ENT300 Apong Cafe / Gary Clinton Ak Churchill Lawi... [et.al] - Churchill Lawi, Gary Clinton; Mohd Ali, Hilmi; Herman, Ted Ouvier; Lawrance, Shamine Ehlaws; Abdul Rahaman, Azlan Faris (2015)
Apong Café is a partnership business which consist of five partners of shareholders. Each Partner contributes certain amount of capital as agreed in agreement. Our company is based on the production of ice cream flavoured by local palm sugar or known by gula apong sugar with variety of topping and determined to become a daily necessity for local ice cream lover around Kuching Especially around Samarahan. Besides that, we also want to provide a comfortable place where people can relax and escape form busy life while having our significant gula apong flavoured ice cream. With growing demand for good texture of taste of ice cream and services. Apong Café tries to attract customers of all stages of ages especially teenagers and groups of workers. Thus, we will offer our customers with spectacular gula apong flavoured ice cream.